Impacts of Plu kaow (Houttuynia cordata Thunb.) Ethanolic Extract on Diabetes and Dyslipidemia in STZ Induced Diabetic Rats: Phytochemical Profiling, Cheminformatics Analyses, and Molecular Docking Studies - Shaikh Shahinur Rahman; Anuwatchakij Klamrak; Napapuch Nopkuesuk; Jaran Nabnueangsap; Piyapon Janpan; Kiattawee Choowongkomon; Jureerut Daduang; Sakda Daduang (MDPI AG, 2024)
The increasing prevalence of diabetes and dyslipidemia poses significant health challenges, impacting millions of people globally and leading to high rates of illness and death. This study aimed to explore the potential antidiabetic and hypolipidemic effects of Plu kaow (Houttuynia cordata Thunb.) ethanolic extract (PK) in streptozotocin (STZ) induced diabetic rats, focusing on its molecular mechanisms. Diabetes was induced in fasting Long Evans rats using streptozotocin (65 mg/kg b. w.), with glibenclamide (5 mg/kg/day) used as the standard experimental drug. The treated groups received oral supplementation of PK (500 mg/kg/day) for 28 days. The study evaluated blood glucose levels, lipid status, body weight, liver, kidney, and heart function biomarkers, antioxidant activity, and histological examination of various organs. Additionally, untargeted metabolomics, cheminformatics, and molecular docking were employed to elucidate the probable mechanisms of action of PK. Based on metabolomic profiling data, the PK was found to contain various putative antidiabetic agents such as kaempferol 7-neohesperidoside, isochlorogenic acid C, rutin, datiscin, and diosmin and they have been proposed to significantly (p < 0.001) reduce blood glucose levels and modulated hyperlipidemia. PK also improved the tested liver, kidney, and heart function biomarkers and reversed damage to normal pancreatic, liver, kidney, and heart cells in histological analysis. In conclusion, PK shows promise as a potential treatment or management option for diabetes and hyperlipidemia, as well as their associated complications in diabetic rats.